Electrohydraulic pulse grinding of radioactive solid NF waste simulation materials - Vinnikov, D.V.; Ponomaryov, A.N.; Tkachov, V.I.; Buravilov, I.V.; Yuferov, V.B. (Вопросы атомной науки и техники, 2016)
A technique used for the grinding of radioactive waste simulation materials using water spark discharges has been proposed. Two modes of the material grinding have been specified. The mass loss of grinded materials versus the amount of pulses and the work volume of electrohydraulic reactor has been compared.